Assessment of the relationship between rectus femoris cross-sectional area and knee extension strength in the prosthesis users with transtibial amputation: A case-control study - YAĞCI, İLKER; GÜNDÜZ, OSMAN HAKAN (My University, 2022)
Objectives: This study aims to investigate cross-sectional area of the amputated-limb rectus femoris compared to the intact-limb and controls and to determine its correlation with functional strength and walking tests in prosthesis users with transtibial amputation. Patients and methods: Between October 2018 and April 2019, a total of 14 prosthesis users (12 males, 2 females; mean age: 47.1 +/- 16.2 years; range, 26 to 73 years) who met the inclusion criteria, and 14 age-, sex-, and dominancy-matched able-bodied controls (12 males, 2 females; mean age: 47.1 +/- 16.2 years; range, 26 to 73 years) were included in this case-control study. Cross-sectional area of rectus femoris (CSA-RF) was evaluated bilaterally by two independent examiners. Knee extension strength was measured bilaterally by using a handheld dynamometer. Functional strength and walking were assessed by Step-Up-Over and Walk-Across tests of the NeuroCom Balance Master (R) device. Results: The CSA-RF was found to be reduced in amputated-limb compared to the intact-limb and able-bodied controls (p<0.01). In the prosthesis users, the cross-sectional area difference between both limbs rectus femoris muscles was shown to be correlated with actual and functional knee extension strength, step length, and walking speed (p<0.05). Intra-and inter-observer reliability of CSA-RF on both sides were found to be good to excellent (intraclass correlation coefficient: 0.856-0.936). Conclusion: Ultrasonographic measurement of CSA-RF is a valid and reliable tool to assess the functional strength and walking in the prosthesis users with unilateral transtibial amputation.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Medicine; Health Sciences; Internal Medicine Sciences; Physical Medicine and Rehabilitation; REHABİLİTASYON; Klinik Tıp; Klinik Tıp (MED); REHABILITATION; CLINICAL MEDICINE; Clinical Medicine (MED); Chiropractics; Rehabilitation; Physical Therapy, Sports Therapy and Rehabilitation; Amputees; muscle strength; rectus femoris; rehabilitation; LOWER-LIMB AMPUTATION; MUSCLE THICKNESS; AMPUTEES; BALANCE; ACCELEROMETER; INDIVIDUALS; CHILDREN; FORCE; Amputees; muscle strength; rectus femoris; rehabilitation